Application of Carbon Paste Electrode Modified with Carbon Nanofibres/Polyaniline/Platinum Nanoparticles as an Electrochemical Sensor for the Determination of Bezafibrate. Issue 3 (23rd January 2018) - Rajpurohit, Anuja S.; Punde, Ninad S.; Rawool, Chaitali R.; Srivastava, Ashwini K.
Abstract: The present study deals with the development of an electrochemical sensor for quantitative determination of Bezafibrate (BZF) based on carbon nanofibers/polyaniline/platinum nanoparticles modified carbon paste electrode (CNF/PANI/Pt/CPE). BZF is a fibric acid derivative and is used largely in the treatment of lipid disorders. The nanocomposite was synthesized by in situ polymerization of aniline using ammonium persulphate and platinum nanoparticles were uniformly decorated on the CNF/PANI surface by reducing hexachloroplatinic acid using sodium borohydride. The electrochemical response of BZF at CNF/PANI/Pt/CPE was studied using cyclic voltammetry (CV), differential pulse voltammetry (DPV) and electrochemical impedance spectroscopy (EIS). The above study resulted into significant improvement of the electrochemical signal towards the oxidation of BZF, revealing that the oxidation process is highly favorable at the surface of modified electrode. The anodic peak current Ip (μA) is found to be linearly dependent on BZF concentration in the range of 0.025 μM to 100 μM with a detection limit of 2.46 nM. The practical analytical utilities of the sensor were investigated by performing the experiments on synthetic pharmaceutical formulations, human blood serum and urine samples which offered good recovery, suggesting the high efficacy and authenticity of CNF/PANI/Pt/CPE sensor for BZF determination. Abstract :